Camouflaged regions conceal critical regions in ATAC‐Seq and Hi‐C sequencing assays, hiding potential contributing factors in Alzheimer's disease. (20th December 2022) - Wadsworth, Mark E; Page, Madeline L; Heberle, Bernardo Aguzzoli; Miller, Justin B; Ebbert, Mark T.W.
Abstract: Background: For many regions of the genome, genetic variants are completely overlooked when using standard short‐read sequencing approaches because of either; (1) lack of coverage (i.e., 'dark‐by‐depth'), or (2) reads aligning to multiple regions (i.e., 'dark‐by‐MAPQ', a.k.a. 'camouflaged' genes). Multiple alignments occur because of genomic duplication events that contribute to molecular evolution, but present major analytical challenges for aligning short‐read sequencing data to the genome. We previously presented a method to identify and differentiate dark and camouflaged regions by analyzing the read depth and reads with multiple alignments. Here we present data demonstrating that not only do camouflaged regions conceal essential genetic variants, but they further conceal results from other short‐read sequencing assays, including ATAC‐Seq and Hi‐C. Our results have important implications for all disease research, including Alzheimer's disease. Methods: We identified and validated genome‐wide camouflaged regions using an updated version of our algorithm to identify camouflaged genomic regions, and then applied it to publicly available ATAC‐Seq and Hi‐C sequencing data sets. Results: We identified 148, 197 camouflaged regions of greater than 20 bases. Of these regions 23.23% overlap at least one Ensembl transcript. Additionally, we found that results for camouflaged regions, including CR1 (a top Alzheimer's disease gene), are also non‐existent in ATAC‐Seq and Hi‐C data. As previously described, we can rescue variants that fall within these regions such as the frameshift we described in CR1. Thereby, we show that including a rescuing step in your alignment pipeline may provide important insights into disease etiology. Conclusion: While short‐read sequencing has been a major boon to research, there are many systematic flaws to using short‐read sequencing, including camouflaged regions. Rescuing variants or peaks in these camouflaged regions could elucidate important findings related to Alzheimer's Disease etiology that are missed by standard short‐read sequencing methods.